Acceptance towards e-learning among university students during Covid-19’S movement control order / Ida Hasni Shaari, Nik Nur Ashyiken Nik Zulfikri and Nur Aina Wahida Saumi - Shaari, Ida Hasni; Nik Zulfikri, Nik Nur Ashyiken; Saumi, Nur Aina Wahida (UiTM Press, 2022)
The implementation of e-learning is highly demanded during the Covid-19 pandemic outbreak. It has been developed to overcome barriers associated with time, space, or geographical location that prevent the students from attending an-on campus course. Overall, previous literature highlighted the benefits and disadvantages of e-learning among school and university students. However, limited studies have evaluated the acceptance level of university students towards e-learning during a restricted environment like a state of emergency like Movement Control Order (MCO) during the Covid-19 pandemic. Therefore, this study aims to explore the acceptance level towards e-learning based on different locations and years of study and to compare the mean difference of acceptance level towards e-learning during the Covid-19 movement control order. A total of 151 undergraduate physiotherapy students were recruited in this study. A quatitative approach was employed through a questionnaire as the research instrument. The findings revealed both urban and rural regions demonstrated moderate acceptance towards e-learning. Students from the first year until the fourth year also showed a moderate acceptance level towards e-learning. Nevertheless, there were no mean differences between locations and years of study with students’ acceptance level towards e-learning. Thus, the acceptance towards e-learning among Physiotherapy students were not affected based on the years of study and geographical locations.